(untitled) (Nigerian Journal of Technology, 2015)
This paper evaluates the optimal cored section of a hollow concrete beam by observing the effect of varying effective flange width and the hollow core position in the compression zone of a plain concrete beam with a point loaded at midspan. Equations were derived using double integration method to determine the moment of inertia of the sections and corresponding deflections as the load increased up to failure, while maintaining a constant cross-sectional area and varying the section dimensions randomly in steps of 10mm from 150mm to 190mm flange width. The results obtained were compared with linearized experimental results. The results showed an increase in the deflection with failure loads of the beam samples as the flange width increased. This study reveals that the 150mm, 160mm, 170mm, 180mm and 190mm, flanged beams had a linear coefficient of 5.25, 9.90, 3.87, 10.62 and 7.23 respectively, and thus concludes that the beam with 170 mm flange width, 46mm core position and 0.58mm deflection at failure of load 15kN is the optimal section. This optimal section corresponds to a beam with a flange width 126.67% its beam width while the core position is about 30.67% into the compression zone which is measured from the remote edge of the flange. Flanged hollow core beams are commonly encountered in high rise structures and bridges. http://dx.doi.org/10.4314/njt.v34i2.1